(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Today, many scientists in modern linguistics have developed a number of new methods for the development of students’ speaking skills and applied them to the educational process. The following article talks about the importance of the “Shadowing” technique, which is considered one of such interactive methods, in the development of the speaking skills of students’ who are learning English. The author gives examples of the advantages and disadvantages of the “Shadowing” technique